Effect of Conjugated Linoleic Acid Supplementation on Serum Leptin Concentration: A Systematic Review and Meta-Analysis - Haghighatdoost, Fahimeh; Hariri, Mitra (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2018)
Background: There are controversies regarding the effect of conjugated linoleic acid (CLA) on serum leptin. Objective: To conduct a meta-analysis of randomized controlled trials (RCTs) to assess the effect of CLA on serum leptin concentrations. Method: Databases such as Ovid, PubMed/Medline, SCOPUS, Google Scholar, and ISI databases up to January 2017 were searched. The searches included RCTs conducted among human adults, and studies on the effect of conjugated linoleic acid on serum leptin concentrations as outcome variables. The mean difference and standard deviation of leptin changes in the intervention and control groups were used as effect size measures for the meta-analysis. Result: Eleven trials with thirteen effect sizes were pooled in this meta-analysis. CLA supplementations could not reduce serum leptin levels significantly (-0.12 (ng/ml); 95% CI: -1.29, 1.05; P=0.837). However, the impact of CLA supplementation differed by sex and BMI status. Compared with the control group, CLA administration reduced serum leptin levels significantly in trials conducted among male (- 0.86 (ng/ml); 95% CI: -1.11, -0.62; P<0.0001) or overweight individuals (-1.37 (ng /ml); 95% CI: -2.55, -0.20; P=0.022) and lasted for less than 8 weeks (-0.90 (ng/ml); 95% CI: -1.64, -0.17; P=0.0.016). Conclusion: CLA supplementation might be able to decrease circulating leptin levels in studies with duration of less than 8 weeks especially among male and overweight subjects. Additional RCTs that are well controlled for energy intakes may be necessary to explain the cause of short- and long-term effects of conjugated linoleic acid. The protocol was registered with PROSPERO (No. CRD42017059165).
Keywords: systematic review